HUBUNGAN KADAR D-DIMER DAN NEUTROFIL LYMPHOCYTE RATIO DENGAN TINGKAT KEPARAHAN COVID-19 DI RS TUGUREJO SEMARANG - Shinta Anjani Putri, Ni Wayan; Wahab, Zulfachmi; Setyoko; Diatri, Devita (Fakultas Kedokteran Universitas Alkhairaat, 2024)
ABSTRACT Treatment and management of blood clotting disorders in Covid-19 patients when they have just been admitted to the hospital must be considered even if no bad manifestations are found due to increased D-dimer levels. Initial indications obtained from the hemostasis laboratory, D-dimer levels are very important to use to calculate the degree of risk and survival of Covid-19 patients. Therefore, this research was carried out with the aim of assessing the relationship between D-dimer levels and Neutrophil lymphocyte ratio with the severity level in Covid-19 patients at Tugurejo Hospital, Semarang. The type of research used in this research is analytical observational with a cross sectional design. This approach was carried out to determine the relationship between D-dimer levels and Neutrophil lymphocyte ratio with the severity of Covid-19 patients at Tugurejo Hospital, Semarang, Central Java. The majority of Covid-19 patients at Tugurejo Hospital Semarang had increased D-Dimer levels, which could indicate a potential disturbance in the blood clotting system. the majority of patients, 95.5%, showed a risky NLR (≥3.3). Most of the patients treated at Tugurejo Hospital Semarang experienced severe levels of severity. There is a significant pattern between the severity of Covid-19 patients and D-Dimer levels, where higher levels of severity tend to be associated with higher D-Dimer levels. There is a significant relationship between NLR and patient severity, with a significance value of 0.000. Research findings show that the majority of Covid-19 patients at Tugurejo Hospital Semarang experienced increased D-Dimer levels, reaching 93.2%. Elevated NLR reflects high levels of inflammation and an active immune system response. serious impact of this disease on the hospital. There is a significant relationship between D-Dimer levels and the severity of Covid-19 patients at Tugurejo Hospital Semarang with a significance of 0.000 or P<0.05 and there is a significant relationship between NLR and the severity of Covid-19 patients with a significance of 0.000 or P< 0.05